Animism in Southeast Asia - Århem, Kaj; Sprenger, Guido; Howell, Signe (Routledge contemporary Southeast Asia series, 2016)
Southeast Asian animism in context / Kaj Arhem -- Dimensions of animism in Southeast Asia / Guido Sprenger -- Seeing and knowing : metamorphosis and the fragility of species in Chewong animistic ideology / Signe Howell -- Graded personhood : human and non-human actors in the Southeast Asian uplands / Guido Sprenger -- Animism and the hunter's dilemma : hunting, sacrifice and asymmetric exchange among the Katu of Vietnam / Kaj Arhem -- Wrestling with spirits, escaping the state : animist ecology and settlement policy in the Annamite Cordillera / Nikolas Arhem -- Actualizing spirits : Ifugao animism as onto-praxis / Jon Henrik Ziegler Remme -- Relatedness and alterity in Bentian human-spirit relations / Kenneth Sillander -- The dynamics of the cosmic conversation : beliefs about spirits among the Kelabit and Penan of the Upper Baram River, Sarawak / Monica Janowski -- Animism and anxiety : religious conversion among the Kelabit of Sarawak / Matthew H. Amster -- Boundaries of humanity : non-human others and animist ontology in eastern Indonesia / Timo Kaartinen -- Gods and spirits in the Wetu Telu religion of Lombok / Sven Cederroth -- Impaling spirit : three categories of ontological domain in eastern Indonesia / David Hicks -- Southeast-Asian animism : a dialogue with Amerindian perspectivism / Kaj Arhem -- End comment : to conclude in the spirit of rebirth, or, A note on animic anthropo-ontogenesis / Tim Ingold.
Keywords: Southeast Asia -- Religious life and customs; Konferenzschrift; Aufsatzsammlung; Animismus; Südostasien